Text Analysis to Enhance Flow of Ideas Fluency and Conjugation Accuracy of EFL Students’ Writing - Rustipa, Katharina; Soepriatmadji, Liliek; Rahayu, Endang Yuliyani; Kasprabowo, Teguh (Universitas Islam Negeri Walisongo Semarang, 2024)
Empirical studies revealed the EFL students’ writing problems, such as incomplete paragraph development and conjugation accuracy. These problems affected the overall text coherence. These problems have inspired teacher researchers to investigate alternative instructional techniques to improve the flow of ideas and conjugation accuracy of EFL students' paragraphs. This current research aims to investigate mood and paragraph structure analysis effectiveness to develop the conjugation accuracy and flow of ideas fluency in EFL students' paragraphs. This study followed an experimental design utilizing control and experimental groups. The research subjects comprised 30 2nd-year undergraduate EFL learners who were at an intermediate level of English proficiency. Data for this research were collected using multiple methods, including tests, documentation, and interviews. The research results revealed that mood analysis and paragraph-structure analysis were effective techniques for improving the conjugation accuracy and idea flow fluency of EFL students' writing. Thus, it is recommended that mood and paragraph structure analyses be alternative techniques to teach paragraph writing.